2008
DOI: 10.1093/bja/aen213
|View full text |Cite
|
Sign up to set email alerts
|

Combination of opioid agonist and agonist–antagonist: patient-controlled analgesia requirement and adverse events among different-ratio morphine and nalbuphine admixtures for postoperative pain

Abstract: The interaction between morphine and nalbuphine in PCA admixture on analgesia is additive. Combinations of morphine and nalbuphine in PCA can decrease the incidence of pruritus, and the antipruritus effect is ratio-dependent. This may provide a novel combination strategy of opioid agonist and agonist-antagonist for postoperative pain management after gynaecologic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 22 publications
4
55
0
3
Order By: Relevance
“…There was no difference in pain scores and side effects between fentanyl-morphine and fentanyl PCA (Friedman et al, 2008 Level II). Beneficial effects on pain relief and the incidence of pruritus in a comparison of morphine, nalbuphine and varying combinations of the two drugs were dependent on the ratio of drugs used (Yeh et al, 2008 Level II). The addition of alfentanil to morphine resulted in no differences in pain relief or adverse effects compared with morphine alone, although patients who received the alfentanil-morphine mixture rated speed of onset and effectiveness of analgesia as better (Ngan Kee et al, 1999 Level II).…”
Section: Chaptermentioning
confidence: 99%
“…There was no difference in pain scores and side effects between fentanyl-morphine and fentanyl PCA (Friedman et al, 2008 Level II). Beneficial effects on pain relief and the incidence of pruritus in a comparison of morphine, nalbuphine and varying combinations of the two drugs were dependent on the ratio of drugs used (Yeh et al, 2008 Level II). The addition of alfentanil to morphine resulted in no differences in pain relief or adverse effects compared with morphine alone, although patients who received the alfentanil-morphine mixture rated speed of onset and effectiveness of analgesia as better (Ngan Kee et al, 1999 Level II).…”
Section: Chaptermentioning
confidence: 99%
“…Many studies have reported that incidence of adverse effects like pruritus and postoperative nausea and vomiting is lower with nalbuphine in comparison with morphine. [4][5][6][7][8][9] Reviews on preclinical pharmacology of this drug suggest that nalbuphine moiety is approximately 10 times more pharmacologically potent than the mixed opioid agonist-antagonist butorphanol on an "antagonist index" scale, which quantitates the drug's ability to act both as an analgesic (via opioid κ-receptor agonism) and as a µ-receptor antagonist. 10 The opioid antagonist activity of nalbuphine is one-fourth as potent as nalorphine and 10 times that of pentazocine.…”
Section: Discussionmentioning
confidence: 99%
“…Analgesic effect is additive and decrease the incidence of pruritis and also antagonize the respiratory depressant activity of other narcotics. (1,2,3,4,5) Nalbuphine is a partial agonist and has its effects at the kappa receptors. This is important as it suggests a ceiling effect is be present in the response produced.…”
Section: Discussionmentioning
confidence: 99%